Local advanced adrenocortical cancer with a long‐term recurrence‐free survival treated with complete surgical excision and adjuvant therapy with a very low‐dose mitotane - Tokura, Yuumi (IJU Case Rep, 2020)
INTRODUCTION: Adrenocortical cancer is a rare tumor with high malignant potential, often resulting in recurrence and poor survival even after complete excision. Thus, adjuvant therapy needs to be considered despite its unestablished effectiveness. CASE PRESENTATION: We report a 70‐year‐old man presented with a huge adrenal mass extending into the right liver lobe. He underwent right adrenalectomy concurrent with right nephrectomy and right hemihepatectomy for curative intent. He was given a very low‐dose mitotane (0.5 g/day) adjuvant therapy to be alive without any signs of recurrence for 90 months after surgery without unwanted toxicity. CONCLUSION: A long‐term and very low dose of adjuvant mitotane could be an option for a patient with complete surgical resection in an expectation to prevent microscopic residual disease from recurrence.